Jewish opposition to Zionism, between anti-racism and anti-colonialism - Guediri, Kaoutar (السفير العربي, 2018)
By refusing the manipulation of Judaism and Jewish identity by the Zionist movement and Israel, the UJFP and other secular Jewish anti-Zionists point up to Zionist ideology and system of domination: ethnic nationalism, racism, capitalism